2013
DOI: 10.1097/nnr.0b013e3182781524
|View full text |Cite
|
Sign up to set email alerts
|

Acupressure Improves Sleep Quality of Psychogeriatric Inpatients

Abstract: Acupressure may be an effective means of improving sleep quality of psychogeriatric inpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
1
19
1
Order By: Relevance
“…Review of the full articles resulted in exclusion of an additional 15 studies. 3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21] Studies were excluded because they did not report self-acupressure, did not directly compare acupressure and placebo/control, did not include extracted clinical outcomes, were duplicate studies, or were not original articles. At the end of the review process, 10 studies (eight RCTs and two quasi-RCTs) out of 793 articles were selected for inclusion in this review ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Review of the full articles resulted in exclusion of an additional 15 studies. 3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21] Studies were excluded because they did not report self-acupressure, did not directly compare acupressure and placebo/control, did not include extracted clinical outcomes, were duplicate studies, or were not original articles. At the end of the review process, 10 studies (eight RCTs and two quasi-RCTs) out of 793 articles were selected for inclusion in this review ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The Chinese Version PSQI was tested and a cut point of greater than 5 was determined to discriminate poor from good sleepers in Taiwanese (Tsai et al, 2005). The Chinese Version PSQI has been widely used in Taiwan (Chen et al, 2015; Lu, Lin, Chen, Tsang, & Su, 2013). To be consistent with the cut point greater than 5, some recent studies in Mainland China also adopted global score greater than 5 as the cutoff to define good and poor sleepers (Li et al, 2012; Luo et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Lu et al . () provided acupressure (involving shenmen, Yangchuan and neiguan) to 60 psychogeriatric inpatients, participants in the study group showed greater improvements ( p < 0·05) in PSQI index than control group after four weeks treatment. Fan et al .…”
Section: Discussionmentioning
confidence: 95%